A Regulatory and Pricing Divergence in Pharmaceutical Markets: EU, Slovenia, U.S. - Heller, Thomas Allan; Turnšek, Ema (Medicine, Law & Society, 2026)
This paper examines the chosen aspects, circumstances and frameworks in the field of pharmaceuticals. The Authors first investigate the role of the U.S., Slovenian and the EU bodies that regulate, monitor and supervise the functioning of the pharmaceutical industries. Both, the EU’s agency EMA and the U.S.’s administration FDA, try to achieve the same purpose – to establish and maintain public health and safety. With their qualifications and power, they greatly contribute to the quality of medicinal products on both markets. However, there is one big difference between them. That is the power over making the medicines available and the setting of prices. While the EMA and for example JAZMP, the Slovenian competent authority, have the control over this financial aspect, FDA does not. The paper further on examines, what are the checks and boundaries for the setting of prices and in this regard, what is regulated within the legislative framework of Slovenia, the EU and the U.S. The fact that health is a fundamental right in EU Member States, but not in the U.S., alone explains the striking divergence in the cost of drugs in the EU as compared to the U.S.
Keywords: pharmaceuticals; pharmaceutical law; setting of drug prices; medicinal products prices; comparison of the US; EU and Slovenian legal framework